Diversitas Gastropoda Berdasarkan Tingkat Kerusakan Mangrove Di Pulau Towea Kabupaten Muna Sulawesi Tenggara - La Ode Adi Parman Rudia; Bahtiar Bahtiar; Jamili Jamili; Muhsin Muhsin; Nasaruddin Nasaruddin (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2019)
The purpose of this study was to find out the diversity index of molluscs (gastropods & bivalves) based on mangrove degradation level in Tobea Island of Muna Regency. The data were collected from May until July 2017, in Wangkolabu municipal area of Tobea sub-district, using observation method and direct observation in the research location to find out the index of ecology of molluscs such as index of diversity (H'), evenness (E), density (N), dominance (D), and dispersion pattern (Id) from both gastropod and bivalve classes based on mangrove degradation level. Direct identification in the field is applied to the type of mangrove vegetation and mollusc organisms that have been known by it’s scientific name. But if not, then the samples are taken and the documentation is then done further analysis at the Laboratory of Biology Unit of Ecology and Taxonomy of FMIPA UHO with reference to the guide book of Introduction of Mangrove in Indonesia and book Snail & Shell Indonesian. Then for water environment parameters in the form of water and substrate samples are further analyzed at Biology Laboratory of UHO Forensic and Biomolecular Unit using Miller triangle fraction method and APHA standard method. Statistical analysis is done using Excel Stat to determine the major components affecting the ecological index of molluscs in degraded mangrove areas. The results showed four species mangroves in Wangkolabu Village are Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, and Sonneratia alba and that mangrove degradation on the coast of Tobea Island, Wangkolabu village, Tobea sub-district has varied values for good mangrove criteria (Density/RDi = 1.600 individuals/hectare), medium mangrove (Density/RDi = 1.175 individuals/hectare), and mangrove broken/rare (Density/RDi = 375 individuals/hectare). Besides that, Cerithium spp., Nerita costata, Terebralia sulcata, and Clypeomorus sp., type gastropods is able to adapt to mangrove forests that have moderate density (RDi= 1.000–1.500 individuals/hectare), with mangrove substrate types in the form of sandy loam that has soil organic content (BO = 3,18%). While the gastropod type Telescopium telescopium prefers low density mangrove forests (RDi < 1.000 individuals/hectare) with the type of substrate in the form of clay containing organic matter (BO = 2,35%).  Based on the results of the study it is expected that the need for mangrove forest management in the study area for the sustainability of aquatic biota, especially molluscs that can be developed as conservation areas by looking at the level of mangrove damage through non-fish aquaculture activities (shellfish) for the welfare of coastal communities and islands small in Southeast Sulawesi.